Whose Bible, mine or yours? Contested ownership and Bible translation in Southern Africa - Jeremy Punt (HTS Teologiese Studies/Theological Studies, 2004)
An important but often neglected aspect of the use of the Bible in Africa is its ownership and issues related thereto. Ownership of the Bible obviously concerns its personal possession and all that that entails, but goes beyond the commodification of the Bible in modern consumerist culture to refer, ultimately, to the control of the biblical texts. The limited attention to the ownership of the Bible is mostly restricted to hermeneutics, often identified as a site of struggle in Africa. However, claims to ownership are becoming increasingly visible and up-front in the area of vernacular translations, where such claims and other conditions imposed on Bible translations illustrate the affinity people have with the Book, how their sense of identity and worldviews are moulded by it and how a Bible translation acts as an important player in issues of power at various levels.